Effect of one month ketoconazole treatment on GH, cortisol and ACTH release after ghrelin, GHRP-6 and GHRH administration in patients with cushings disease - Correa-Silva,Silvia R. (2007)
GH responses to ghrelin, GHRP-6, and GHRH in Cushings disease (CD) are markedly blunted. There is no data about the effect of reduction of cortisol levels with steroidogenesis inhibitors, like ketoconazole, on GH secretion in CD. ACTH levels during ketoconazole treatment are controversial. The aims of this study were to compare the GH response to ghrelin, GHRP-6, and GHRH, and the ACTH and cortisol responses to ghrelin and GHRP-6 before and after one month of ketoconazole treatment in 6 untreated patients with CD. Before treatment peak GH (mg/L; mean ± SEM) after ghrelin, GHRP-6, and GHRH administration was 10.0 ± 4.5; 3.8 ± 1.6, and 0.6 ± 0.2, respectively. After one month of ketoconazole there was a significant decrease in urinary cortisol values (mean reduction: 75%), but GH responses did not change (7.0 ± 2.0; 3.1 ± 0.8; 0.9 ± 0.2, respectively). After treatment, there was a significant reduction in cortisol (mg/dL) responses to ghrelin (before: 30.6 ± 5.2; after: 24.2 ± 5.1). No significant changes in ACTH (pg/mL) responses before (ghrelin: 210.9 ± 69.9; GHRP-6: 199.8 ± 88.8) and after treatment (ghrelin: 159.7 ± 40.3; GHRP-6: 227 ± 127.2) were observed. In conclusion, after short-term ketoconazole treatment there are no changes in GH or ACTH responses, despite a major decrease of cortisol levels. A longer period of treatment might be necessary for the recovery of pituitary function.